2015
DOI: 10.1109/tdei.2015.7076790
|View full text |Cite
|
Sign up to set email alerts
|

The effect of resin stoichiometry and nanoparticle addition on epoxy/silica nanodielectrics

Abstract: Epoxy-based systems are used widely as dielectrics in electrical applications and, in such systems, the chosen stoichiometry is important in determining the nature of the molecular network that forms and, hence, the physical properties of the final system. However, the inclusion of nanoparticles with large interfacial areas into epoxy systems may introduce additional chemical reactions between moieties on the nanoparticle surfaces and the reactants, or may alter the rate and sequence of the various chemical pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 61 publications
4
17
0
Order By: Relevance
“…To test this assertion, the change in the heat capacity, Δ C p , across the glass transition was determined for all samples and the effect of surface functionalization on this quantity is shown in Figure 4b. Where T g is high in Figure 4a, generally, Δ C p is low in Figure 4b; this anti-correlation is consistent with effects seen elsewhere in comparable systems [18], suggesting that the associated variations in T g are indeed significant. Significant variations in the parameter Δ C p have been seen in polyurethane-based nanocomposites containing organically modified montmorillonite (MMT), where a monotonic reduction in Δ C p was seen as the volume of MMT in the system increased (0–5.7 vol %) [31].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…To test this assertion, the change in the heat capacity, Δ C p , across the glass transition was determined for all samples and the effect of surface functionalization on this quantity is shown in Figure 4b. Where T g is high in Figure 4a, generally, Δ C p is low in Figure 4b; this anti-correlation is consistent with effects seen elsewhere in comparable systems [18], suggesting that the associated variations in T g are indeed significant. Significant variations in the parameter Δ C p have been seen in polyurethane-based nanocomposites containing organically modified montmorillonite (MMT), where a monotonic reduction in Δ C p was seen as the volume of MMT in the system increased (0–5.7 vol %) [31].…”
Section: Resultssupporting
confidence: 85%
“…In the work of Nguyen et al [18], the nanosilica was introduced using a proprietary masterbatch system, Nanopox E 470 (supplied by Nanoresins), where the nanosilica is described as consisting of an agglomerate-free colloidal dispersion of surface-modified synthetic SiO 2 with an average particle diameter of 20 nm. It is evident from the study of Nguyen et al [18] that it is possible to produce agglomerate-free materials through the use of systems such as Nanopox E 470, albeit that this comes at the cost of neither knowing the nanofiller surface chemistry nor being able to modify it as required.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, a number of reported studies have considered the effect of network structure and resin/hardener stoichiometry on mechanical properties [3][4][5][6][7][8][9]. However, very few studies of the effects of stoichiometry on dielectric properties have been reported [10]. Changing the resin/hardener ratio results in changes in the crosslinking density and, consequently, the network structure of the cured epoxy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, analyzing the effect of resin/hardener stoichiometry on the electrical properties can give insights on how the network structure and the chemical composition each affect the electrical behavior of the bulk material. In the last two decades a burgeoning interest has been shown in enhancing the dielectric performance of epoxy networks by filling them with a range of nanofillers, such as silica [10,11], boron nitride [12,13] and silicon nitride [14]. Nanofillers are characterized by their high surface area and are often covered with different functional groups, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…T g decreased slightly with increasing filler loads—however, the changes in T g did not vary systematically with the composition, and the authors concluded that this invariance in the range of T g indicated that there are no interfacial regions with filler–matrix interactions affecting the chain dynamics in the bulk polymer. Yeung and Vaughan also highlighted results from Nguyen et al, which showed that T g does vary systematically with changing stoichiometric ratio of epoxy to anhydride (hardener).…”
Section: The Structure–property Relations In Epoxy Nanocompositesmentioning
confidence: 83%